EFFECT OF HERBICIDES ON WEED CONTROL IN POTATO - Singh, Vijay Pal; Nehra, B K; Khurana, S. C (Potato Journal, 2013)
There were 15 treatments viz., linuron at 0.75, 1.0 and 1.5 kg/ha; metribuzin at 0.25, 0.50 and 0.75 kg/ha; linuron + metribuzin (2:1) and (3:1) ratio both at 0.75, 1.0 and 1.5 kg/ha, along with weeding + earthing up done at 25 DAP, weed free and weedy check. All the herbicides were applied at seven days after planting. All weed control treatments significantly improved total tuber yield as well as total number of tubers per unit area as compared to weedy check. Linuron 1.0 recorded maximum number of tubers per unit area and it was closely followed by metribuzin 0.5. Maximum tuber yield was recorded in linuron 1.0, which was followed by metribuzin 0.5 kg/ha. Combination of linuron and metribuzin in both ratios (2:1 or 3:1) reduced tuber yield in comparison to linuron alone.